The Relationship between Self-Efficacy and Self-Management among Teenager with Asthma: A Systematic Review - Eva Supriatin; Agus Hendra; Tintin Supriatin; Linlin Lindayani (Journal of Nursing Care, 2021)
Asthma is a chronic reactive airway disease caused by a variety of variables, one of which is psychological. Adolescents are prone to psychological issues. Adolescents frequently face difficulties and feel frustrated as a result of the conditions they face, but most adolescents employ a variety of strategies to overcome the problems that arise. Self-efficacy can lead to good self-management. To investigate the relationship between self-efficacy and self-management in asthmatic teenagers. The search strategy is to conduct Pubmed and Google Scholar s for articles that have been published. The term "asthma" is a combination of the words "adolescents" and "self-efficacy" and "self-management" The search criteria were as follows: research on asthma patients who were teenagers, published between 31th January 2004 and July 20 2020, in English, full text, and of quantitative nature. A cross-sectional study evaluated each article for quality using a standard format from The Joanna Briggs Institute Critical Appraisal Tools (JBI). Only five articles were found that matched the search criteria. The relationship between self-efficacy and self-management were found to be associated inconsistent. Four studies reported significantly associated, while one study found no significant correlation between self-efficacy and self-management in asthmatic teenagers. Efficacy has an effect on self-management in adolescents with asthma. Adolescents with asthma must have a high level of self-efficacy to feel more confident in dealing with their situation, make positive changes, and maintain reasonable asthma control.